Mitotane dosage, plasma levels, and anthropometric measurements in pediatric adrenocortical carcinoma - Riedmeier, Maria; Frey, Heidi; Antonini, Sonir R.; Fernandes Luiz Canali; Gabriela; Classen, Carl Friedrich; Domínguez-Pinilla, Nerea; Fassnacht, Martin; Finger, Jasmin; Fuchs, Steffen; Grönroos, Marika; Halah, Mariana P.; et al. (Bioscientifica, 2026)
Objective
Mitotane is an effective treatment for advanced adrenocortical carcinoma (ACC). Given the limited pediatric data available, this study aims to evaluate the associations between mitotane dosage, plasma drug levels, and anthropometric measurements, as well as their potential impact on dosage requirements to optimize therapeutic outcomes in pediatric patients with ACC (pACC).
Design and methods
A retrospective, international, multicenter study was conducted on pediatric ACC patients treated with mitotane across 18 centers. Mitotane serum levels were obtained from the Lysosafe Online® database or directly from the centers. Data from the cohort with plasma levels within the target range (≥14 mg/L; n = 319) were analyzed and compared to those with levels outside this range (n = 320).
Results
Fifty pediatric patients (60% female) diagnosed between 2004 and 2023 were included, with a median follow-up of 34.5 months and a 10-year overall survival of 33 months. The median age at diagnosis was 8.6 years, with most tumors (84%) hormone-secreting. Among 49 patients undergoing surgery, 31 (62%) achieved R0 resection. The median treatment duration was 18 months, with a median mitotane dose of 87 mg/kg/day in patients within the target plasma level range, showing no significant difference from those outside the range. However, BMI was significantly associated with doses of plasma levels in target range (P = 0.001), as underweight (105.4 mg/kg/day) and healthy weight patients (98.4 mg/kg/day) required higher doses than overweight/obese patients (44.4 mg/kg/day). No significant differences in daily dose levels (mg/kg/day and mg/m2/day) were observed based on body weight.
Conclusion
This study supports estimating mitotane dosages in pediatric ACC, emphasizing the need for close monitoring and frequent follow-ups at specialized centers due to individualized dosing and a narrow therapeutic window.